2010
DOI: 10.1039/c003084h
|View full text |Cite
|
Sign up to set email alerts
|

Coordination polymer particles as potential drug delivery systems

Abstract: Micro-and nanoscale coordination polymer particles can be used for encapsulating and delivering drugs. In vitro cancer cell cytotoxicity assays showed that these capsules readily release doxorubicin, which shows anticancer efficacy. The results from this work open up new avenues for metal-organic capsules to be used as potential drug delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(143 citation statements)
references
References 28 publications
2
140
0
1
Order By: Relevance
“…[35,[52][53] Consequently, it is not surprising that microprobe SRXRF is becoming recognised as a technique for imaging intracellular nanoparticles in efforts to develop and confirm the capabilities of these agents. [35,52] An exciting study has been reported by Paunesku et al [52] whereby they aimed to produce DNA-targeting TiO 2 nanoparticles that could be excited, causing the electropositive holes of the semiconductor to be injected into the DNA, ultimately leading to DNA scission.…”
Section: Nanoparticles and Nanoconjugatesmentioning
confidence: 99%
“…[35,[52][53] Consequently, it is not surprising that microprobe SRXRF is becoming recognised as a technique for imaging intracellular nanoparticles in efforts to develop and confirm the capabilities of these agents. [35,52] An exciting study has been reported by Paunesku et al [52] whereby they aimed to produce DNA-targeting TiO 2 nanoparticles that could be excited, causing the electropositive holes of the semiconductor to be injected into the DNA, ultimately leading to DNA scission.…”
Section: Nanoparticles and Nanoconjugatesmentioning
confidence: 99%
“…26,70 Previous papers have reported that the toxicity of raw materials was a key factor to effect on the cytotoxicity of the resulting MOFs. Imaz et al 71 used Zn 2+ metal ions and 1,4-bis(imidazol-l-ylmethyl)benzene organic ligands with low toxicity to structure Zn-based MOFs. It was concluded that these nanoparticles did not show any cytotoxicity in vitro, after they were evaluated on human promyelocytic leukemia cells (HL60) for 24 and 48 hours.…”
Section: Biocompatibility Of Mofsmentioning
confidence: 99%
“…Such biologically and environmentally compatible MOFs are designed and constructed based on specific composition criteria governed by judiciously selecting metal ions and organic linkers as building blocks, which are nontoxic and biologically and environmentally compatible. Biomolecules such as amino acids, peptides, proteins, nucleobases, carbohydrates, and other natural products such as cyclodextrins, porphines, and some carboxylic acids ( Figure 5) serve as emerging building blocks for the design and construction of metal-biomolecule frameworks with novel and interesting properties and applications that cannot be obtained through the use of traditional organic linkers [17,43,44,48,49]. …”
Section: Metal Biomolecule Framework (Biomofs)mentioning
confidence: 99%
“…They also bear the ability to systematically vary and functionalize their pore structure [2,3]. In the history of MOFs, a benchmark was represented by the synthesis of MOF-5 (Zn 4 O(bdc) 3 , bdc = terephthalate) and HKUST-1 (Cu 3 (btc) 2 , btc = 1,3,5-benzenetricarboxylate) with high porosity and low pressure gas sorption, followed by the development of chromium(III) terephthalate (MIL-101) with high chemical stability, MOF-74 (Zn 2 (dhbdc), dhbdc = 2,5-dihydroxy-1,4-benzenedicarboxylate) with low pressure adsorption of CO 2 , and several isostructural analogs of Mg-MOF-74 termed as IRMOF-74-I to IRMOF-74-XI, with large pore apertures to accommodate protein, NU-110E with acetyleneexpanded hexatopic linker, having material highest experimental Brunauer-Emmett-Teller (BET) surface area of any porous material reported to date (7140 m Table 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. …”
Section: Introductionmentioning
confidence: 99%